Eco-theology in action: Addressing the climate crisis through the Sunan Kalijaga Waste Charity Program - Siti Aminah; Aziz Muslim (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
Waste management has become a crucial issue in climate change mitigation. The Sunan Kalijaga Waste Charity Program (PUSAKA) at UIN Sunan Kalijaga Yogyakarta represents an innovative model that integrates Islamic eco-theological values, particularly the concept of sedekah sampah (waste charity) into a participatory campus waste management system. This study employs Participatory Action Research (PAR) to explore how Islamic values shape ecological awareness and collective action in campus waste management. The findings demonstrate that PUSAKA successfully increased environmental awareness, reduced the volume of campus waste, and critically built spirituality-based intrinsic motivation that proved more resilient than purely regulatory or technical approaches. The integration of the concept of waste as an act of worship (ibadah) within the framework of Islamic Eco-Theology (Eco-Fiqh) fostered a deeper ecological consciousness and addressed the social loafing phenomenon prevalent in collective waste management. This study recommends the PUSAKA model for replication at other Islamic higher education institutions and calls for formal institutionalization through binding campus policies, adequate infrastructure, and a participatory monitoring system.